الخطابة الدينية في العصر الأيوبي وأثرها في التعبئة الجهادية: القاضي محي الدين بن الزكي وخطبة الفتح أنموذجا (دراسة أدبية تحليلية) (Comprehensive Journal of Science, 2026)
This research seeks to elucidate the pivotal role of the Minbar (pulpit) as a strategic media tool in managing the existential conflict and reclaiming sanctities during the Ayyubid era. Titled Religious Rhetoric in the Ayyubid Era and its Impact on Jihadist Mobilization: Judge Muhyi al-Din ibn al-Zaki and the Conquest Sermon as a Model (An Analytical Literary Study), the study aims to establish the functional role of rhetoric as a restorative mechanism. It analyzes the stylistic and aesthetic characteristics of Ibn al-Zaki's work while refuting claims of literary stagnation during that period. Furthermore, it examines the mechanisms of intertextuality in fusing religious references within the discourse. The research employs an integrated methodological approach, combining descriptive-analytical methods to deconstruct textual structures, the historical method to contextualize the discourse within its field, and the stylistic method to investigate phonetic and semantic levels, leading to a modern pragmatic approach to analyze the performative power of the word. The study yields several significant results, most notably: that Ayyubid rhetoric transcended traditional preaching to become an integrated media institution sharing in the victory; and that Ibn al-Zaki’s rhetorical embellishments were a conscious acoustic engineering serving mobilization purposes rather than mere verbal luxury. The research also demonstrates the orator’s ability to achieve absorptive intertextuality with the Holy Qur'an, bestowing sanctity upon the event of the conquest. The results confirm Ibn al-Zaki’s success in employing discourse pragmatics and the poetics of space, transforming the landmarks of Jerusalem from silent geographical spaces into living symbols that shape identity and dignity. Finally, the study recommends the necessity of re-reading medieval prose according to modern critical approaches that do justice to its functional aesthetics and reveal the genius of its creators.